Multi-Item Auctions - Demange, Gabrielle; Gale, David; Sotomayor, Marilda (Journal of Political Economy, 1986)
A collection of items is to be distributed among several bidders, and each bidder is to receive at most one item. Assuming that the bidders place some monetary value on each of the items, it has been shown that there is a unique vector of equilibrium prices that is optimal, in a suitable sense, for the bidders. In this paper we describe two dynamic auction mechanisms: one achieves this equilibrium and the other approximates it to any desired degree of accuracy.